ANALISIS PENGARUH GROWTH, FIRM SIZE, EARNING VOLATILITY, TANGIBILITY, ROA, DAN LIQUIDITY TERHADAP RASIO SOLVABILITAS (Studi Empiris pada Seluruh Perusahaan Transportasi di Indonesia yang Tercatat di BEI Periode 2015-2019) - Nisa, Marsya Ainun; Wahyudi, Sugeng (Diponegoro Journal of Management, 2021)
ABSTRACT The purpose of this research to determine any factors that influencing Company Growth (GROWTH), Firm Size (FSIZE), Earning Volatility (EVOL), Tangibility (TAN), Return on Assets (ROA), and Liquidity (LIQ) to the level of Solvency of ratio with 2 calculation of 2 ratio are Debt to Asset (DTA) and Debt to Equity (DTE) for transportation companies in Indonesia. This study uses secondary data that obtained from the annual financial reports of transportation companies that listed on Indonesia Stock Exchange (IDX) during 2015-2019. The total sampel used in this study was 30 samples with the purposive sampling method, that a total of 150 observations were obtained for each dependent variable. This study uses panel data regression method with Eviews 10 program to test the factors that affecting the solvency ratio on the sample. The result from this study is to indicating that FSIZE and LIQ have negative and significant effect on high or low DTA. Inn addition, the results showed that TAN had a negative and significant effect on changes in the level of DTE ratio. But negative and insignificant effect for DTA. The ROA variable has a positive and significant effect on the level of DTA ratio, on the other hand there is a negative and insignificant result on DTE. Meanwhile, the GROWTH and EVOL variables showed no significant effect on the level of the solvency ratio.